E-learning as a Learning Media in the Form of Educational Games for Elementary School Students - Widya Hartayu; Ilham Albana (Journal of Multimedia Trend and Technology, 2023)
The use of games as a means of education is not wrong. Because games are entertaining. Human psychology is more like playing than a serious study. In games, education is given through practice or learning by doing. The aim of this research is to design and build an Educational Game for learning mathematics, sub-materials for addition, subtraction, multiplication, and division on integers, Indonesian, Natural Sciences, Desktop-based IPS, class VI. The purpose of designing this platform is to conceptualize and build E-learning in learning math operations, the Indonesian language, Natural Sciences, Desktop-based IPS, sub-material addition, subtraction, multiplication, and division of integers. Memorizing history and understanding nature and others as well as understanding correct punctuation and language. Data collection methods used are interviews, literature, and documentation. The system development method used is MDLC (Multimedia Development Life Cycle). Its manufacturer uses Adobe Flash Professional CS6, Adobe Photoshop CS6, and Adobe Audition CS6 software. The results of this study are in the form of E-learning as Learning Media in the Form of Educational Games for Class VI Students of SD Negeri 03 Karanggude Kulon